The Development of Vocabulary Learning Achievement and Retention Using Mnemonics and Vocabulary Picture Books For Grade 6 Students of Anuban Nakhon Pathom School - Platapiantong, Theewara; Thienpermpool, Patteera (Journal of Multidisciplinary in Humanities and Social Sciences, 2020)
This Article aimed to: 1) compare the students’ vocabulary learning achievement before and after learning by mnemonic and vocabulary books; 2) study the retention of students after learning by using mnemonics and vocabulary picture books; 3) explore the students’ opinions toward teaching by using mnemonics and vocabulary picture books. The sample was 33 grade 6 students in Anuban Nakhon Pathom School. They were randomly selected. Pre-Experimental Research Design and One-group Pretest Posttest Design are used in this research. The duration of the experiment was 2 weeks. The instruments consisted of 1) lesson plans 3) a vocabulary test 4) a questionnaire on opinions toward learning by using mnemonics and vocabulary picture books. The research results were 1) the students’ vocabulary learning achievement after using mnemonics and vocabulary picture books was significantly higher than before at the .05 level; 2) the students’ opinions toward teaching vocabulary using mnemonics and vocabulary picture books were at the highest level and 3) the students’ retention in teaching vocabulary using mnemonics and vocabulary picture books was not different from the post-test.